Teologi Hassan Hanafi - Shobih, Muhammad (Maliki Interdisciplinary Journal, 2024)
This article discusses the story of a philosopher named Hassan Hanafi. He focuses on traditional theologies and the development of theologies that are more inclusive and relevant to social life. Several of Hasan Hanafi’s works highlight ideas about pluralism, democracy, feminism and inter-religious dialogue. He has tried to embrace a more open and inclusive approach to the understanding of Islam, taking into account the current cultural and social context. Hassan Hanafi’s thought has had a significant impact on the field of modern Islamic theology. Some of the impacts of his thinking can include renewal of Islamic thought, pluralist approaches, social thought, and influence on the younger generation. So this influences the emergence of critical thinking, pluralism and tolerance, Islamic feminism, religious dialogue and social reform.